2022
DOI: 10.3390/en15103843
|View full text |Cite
|
Sign up to set email alerts
|

Benefits Achieved by Energy Suppliers through Cooperation with Individual Recipients and Their Readiness for This Cooperation

Abstract: The aim of this article is to identify the benefits perceived by individual recipients that are achieved by consumer energy suppliers on the market, through multilateral trade cooperation, and to define the structure of these benefits according to the declared readiness of recipients to cooperate with the suppliers. The results of the analysis of the available literature on the subject indicate that there is a cognitive and research gap in relation to the perceived benefits achieved by the suppliers through jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 67 publications
(74 reference statements)
1
1
0
Order By: Relevance
“…et al [53] found that government departments and social capital sectors can gain more benefits after adopting the cooperative model. The same is true for the general contractor and subcontractor; both of them can only cooperate to obtain the maximum benefit, and the optimal outcome of both sides of the game many times is cooperation [54], which is consistent with reality.…”
Section: Discussionsupporting
confidence: 66%
“…et al [53] found that government departments and social capital sectors can gain more benefits after adopting the cooperative model. The same is true for the general contractor and subcontractor; both of them can only cooperate to obtain the maximum benefit, and the optimal outcome of both sides of the game many times is cooperation [54], which is consistent with reality.…”
Section: Discussionsupporting
confidence: 66%
“…Expanding the scope of previous activity by buyers and/or undertaking completely new forms of market activity additionally motivates them to enter new areas of non-purchasing behavior, making individual buyers more engaged and aware of market participants [4]. Thus, they become potentially even more valuable partners for energy suppliers, enriching their market potential and, thus, competitiveness, as A. Baruk and M. Grzesiak write in their article 'Benefits Achieved by Energy Suppliers through Cooperation with Individual Recipients and Their Readiness for This Cooperation' [5].…”
mentioning
confidence: 99%